(3fXQjGJ GdJfejI hfeh GSJQGJjLjGJ GdJfejIs - (3GSeGYjd(B, (3TYHGfjs ((3GdLRGFQ(B:s (3OGQ gheI ddfTQ hGdJhRjY(B,s, 2004)
(3fXQjGJ GdJNda(B- (3fXQjGJ GdJfejI hGdfeh(B- (3GdJfejI GdbOjeI(B- (3fXQjGJ GdJfejI hGdfeh GdMOjKI(B- (3GSJQGJjLjGJ GdJfejI aj HYV GdOhd MOjKI GdJUfjYs
Keywords: (3GdJfejI GdEbJUGOjI(B- (3fXQjGJs